Improving Students’ Motivation in English Learning through Positive Reinforcement - Aulia, Aulia Fatimannisa; Jamilah, Jamilah (International Journal of Contemporary Studies in Education, 2024)
This action research was aimed at improving students' motivation in English learning through positive reinforcement at SMK Prima Mandiri Sejahtera Makassar for the eleventh grade in the academic year of 2022/2023.This research was action research and consisted of two cycles in three meetings. The participants of this research were the eleventh-grade students of SMK Prima Mandiri Sejahtera Makassar in the academic year 2022/2023. The participants consisted of 20 students. The procedures of this research were planning, action, observation, and reflection. The techniques for collecting data were questionnaires, observations, and interviews. In analyzing the data, the researcher did three steps: organizing the data, coding and reducing data, and interpreting data. The validity of the data was obtained by applying democratic validity, outcomes validity, process validity, catalytic validity, and dialogic validity. The reliability of the data was obtained by using time triangulation.The use of positive reinforcement in this study successfully improved the students' motivation. The improvement in student motivation can be seen in enthusiasm, excitement, interest in learning, and curiosity in English learning. The students who were classified as students with low motivation successfully improved their motivation after implementing verbal and non-verbal positive reinforcement. The improvement could be seen from the observation during the process of the action, interview, and the result of the questionnaire. It can be concluded that positive reinforcement can improve students' motivation in English learning